Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphys.2019.00421
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Birds Flock? A Role for Opioids in the Reinforcement of Gregarious Social Interactions

Abstract: The formation of social groups provides safety and opportunities for individuals to develop and practice important social skills. However, joining a social group does not result in any form of obvious, immediate reinforcement (e.g., it does not result in immediate copulation or a food reward), and individuals often remain in social groups despite agonistic responses from conspecifics. Much is known about neural and endocrine mechanisms underlying the motivation to perform mate- or offspring-directed behaviors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 193 publications
1
20
0
Order By: Relevance
“…Opioids in the MPOA of songbirds act to stimulate and maintain affiliative, nonsexual vocal-social interactions. 1,53,54 The present study extended research findings on this type of affiliative, rewarding social behavior from songbirds to rats. Using an IEG expression approach, we found that social play behaviors were associated with a robust increase in expression of Egr1 in the MPOA.…”
Section: Discussionsupporting
confidence: 75%
“…Opioids in the MPOA of songbirds act to stimulate and maintain affiliative, nonsexual vocal-social interactions. 1,53,54 The present study extended research findings on this type of affiliative, rewarding social behavior from songbirds to rats. Using an IEG expression approach, we found that social play behaviors were associated with a robust increase in expression of Egr1 in the MPOA.…”
Section: Discussionsupporting
confidence: 75%
“…Song in this context is facilitated by the presence of flock mates ( Gochfeld, 1977 ; Petrinovich, 1988 ; Jesse and Riebel, 2012 ), but unlike sexually motivated song it is commonly produced by birds facing away from other birds and it appears to be ignored ( Feare, 1984 ; Zann, 1996 ; Riters et al, 2000 ). The immediate function of song in these flocks is not clear, but it is important for song learning and practice and proposed to play a role in flock cohesion ( Riters et al, 2019 ). This is a type of song commonly referred to as undirected song in zebra finches ( Dunn and Zann, 1996 ).…”
Section: Birdsong As An Expression Of Intrinsic Positive Emotionmentioning
confidence: 99%
“…Many bird species form remarkable flocks, often outside the context of breeding, that offer protection from predators and increase foraging efficiency ( Powell, 1974 ; Sullivan, 1984 ). It has been proposed that such large social groups may be maintained by rewarding positive interactions with conspecifics and by reducing negative states caused by social separation ( Emlen, 1952 ; Riters et al, 2019a ). Moreover, within a flock optimal social spacing between conspecifics is important, indicating that individuals may optimize spacing to be close but not too close to conspecifics.…”
Section: Introductionmentioning
confidence: 99%